Um olhar sobre a obra de Milton Santos - Sepúlveda, David Alejandro (Sustainability in Debate, 2015)
Antônio C. R Moraes. Território na Geografia de Milton Santos. São Paulo: Annablume, 2013. 130 p. ISBN: 798-85-391-0526-7